Importance of Continuous Sequential Chemotherapy and Multimodal Treatment for Advanced Testicular Cancer. Issue 11 (March 2015) - Nakamura, Terukazu; Ueda, Takashi; Oishi, Masakatsu; Nakanishi, Hiroyuki; Shiraishi, Takumi; Fujihara, Atsuko; Naito, Yasuyuki; Kamoi, Kazumi; Naya, Yoshio; Hongo, Fumiya; Okihara, Koji; Miki, Tsuneharu; et al.
<x xml:space="preserve">Abstract</x> Abstract Patients with "difficult-to-treat" advanced testicular cancer can require multiple therapies. We retrospectively assessed our patients with advanced germ cell tumors (GCTs) and characterized the clinical efficacy, outcomes, and factors affecting overall survival (OS). Two hundred fifty-three patients with advanced GCTs were treated at Kyoto Prefectural University of Medicine, Kyoto, Japan, from June 1998 to September 2013. Of 253 patients, 142 patients had salvage chemotherapy. As first-line therapy, bleomycin, etoposide, and cisplatin, and etoposide and cisplatin therapies were performed in 234 cases (92.5%). As second-line therapy, etoposide, ifosfamide, and cisplatin/vinblastine, ifosfamide, and cisplatin, and paclitaxel, ifosfamide, and cisplatin/paclitaxel, ifosfamide, and nedaplatin therapies were carried out in 44 and 59 cases, respectively. Furthermore, 111, 72, 44, and 28 cases had third, fourth, fifth, and sixth-or-later-line chemotherapy, respectively. Five-year OS rate stratified by chemotherapy line was 95.5% in the first line, 89.4% in the second line, 82.1% in the third line, 45.1% in the fourth line, and 58.9% in the fifth or after line. A statistical significant difference was found when comparing fourth-or-after-line versus first to third-line therapy. Additional procedures were performed, including retroperitoneal lymph node dissection (RPLND) (n = 168), extra-RPLN resection (n = 114), and external beam radiotherapy/stereotactic radiotherapy (n = 78). Multivariate analysis showed that factors predicting better outcomes were in serum tumor marker (STM) normalization, RPLND, and extra-RPLN resection. Good outcomes were obtained in patients who completed chemotherapy up to third line. After fourth-line chemotherapy, approximately 50% of "difficult-to-treat" patients could be cured with normalization of STM levels and residual mass resection. Continuous or sequential chemotherapy with multimodality therapy is important for patients with "difficult-to-treat" advanced GCTs. Effective chemotherapy after third line should be developed.